An Application of Potential Estimates to A Priori Bounds for Elliptic Equations - Farman Mamedov; Sara Monsurrò; Maria Transirico (Abstract and Applied Analysis)
A potential estimate type approach is used in order to obtain some a priori bounds for the solutions of certain classes of Dirichlet problems associated with nondivergence structure elliptic equations.